2015
DOI: 10.1007/s11356-015-5614-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and applications of a DNA labeling method with magnetic nanoparticles to study the role of horizontal gene transfer events between bacteria in soil pollutant bioremediation processes

Abstract: Horizontal gene transfers are critical mechanisms of bacterial evolution and adaptation that are involved to a significant level in the degradation of toxic molecules such as xenobiotic pesticides. However, understanding how these mechanisms are regulated in situ and how they could be used by man to increase the degradation potential of soil microbes is compromised by conceptual and technical limitations. This includes the physical and chemical complexity and heterogeneity in such environments leading to an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Burmeister et al (2018) found that P. putida was not able to produce yellow fluorescence when bacteria were cocultured in a space-separated device, while contact between the cells caused a change in the fluorescent signal from red to yellow, indicating the occurrence of HGT. Pivetal et al (2015) designed a new microfluidic system composed of micromagnets to monitor HGT. Magnetic nanoparticles were used to label plasmid DNA molecules and magnetic microfluidic devices were then employed to capture and separate the recombinant cells with nanoparticle signals.…”
Section: Horizontal Gene Transfer Of Bacteria Based On Fluorescent Labelingmentioning
confidence: 99%
“…Burmeister et al (2018) found that P. putida was not able to produce yellow fluorescence when bacteria were cocultured in a space-separated device, while contact between the cells caused a change in the fluorescent signal from red to yellow, indicating the occurrence of HGT. Pivetal et al (2015) designed a new microfluidic system composed of micromagnets to monitor HGT. Magnetic nanoparticles were used to label plasmid DNA molecules and magnetic microfluidic devices were then employed to capture and separate the recombinant cells with nanoparticle signals.…”
Section: Horizontal Gene Transfer Of Bacteria Based On Fluorescent Labelingmentioning
confidence: 99%
“…Solid-phase protocols allow more efficient NA isolation than other methods [16,18,28]. Magnetic solid-phase extraction (MSPE) is a fast and easy procedure with high NA yield and purity [18,26,[31][32][33][34][35][36][37][38][39][40][41]. MSPE may be an automated method for NA microextraction without specific equipment [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, in 1996, a relatively more compact device had been developed for sorting and trapping human peripheral lymphocytes tagged with ferromagnetic particles [47]. However, because of the aforementioned reasons on the need for small-scale devices (Lab-on-chip) alongside the advances in synthesis techniques like lithography, researchers' focus shifted towards micro-and millimeter-size permanent magnets [22,[48][49][50][51][52][53][54][55][56][57][58][59][60]. Moreover, reducing the size of the magnets increases the magnitude of the magnetic field gradient [43], ergo, more magnetic particles could be separated/trapped.…”
Section: Introductionmentioning
confidence: 99%